Review of heat transfer fluids in tube-receivers used in concentrating solar thermal systems: Properties and heat transfer coefficients. (March 2016) - Benoit, H.; Spreafico, L.; Gauthier, D.; Flamant, G.
Abstract: The Heat transfer fluid (HTF) is a key component of solar thermal power plant because it significantly impacts the receiver efficiency, determines the type of thermodynamic cycle and the performance it can achieve, and determines the thermal energy storage technology that must be used. This paper reviews current and future liquid, gas, supercritical, two-phase and particulate HTFs. Thermophysical properties are presented as well as correlations to determine the receiver tube-HTF heat transfer coefficients. Variations of convective heat transfer coefficients as a function of temperature are illustrated for all selected HTFs in their stable operation temperature ranges. Finally, recent developments on new HTFs working at 700 °C and beyond are discussed.